2021
DOI: 10.1016/j.omto.2021.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA SERPINE2 promotes development of glioblastoma by regulating the miR-361-3p/miR-324-5p/BCL2 signaling pathway

Abstract: Circular RNA (circRNA) is a new type of long-sequence RNA formed by a noncanonical form of alternative splicing called back-splicing. Emerging evidence has revealed that circRNAs are involved in cancer progression, regulating cancer-related genes through sponging microRNAs (miRNAs). In our study, we identified a novel upregulated circRNA, circSERPINE2 , through analyzing circRNAs microarray data of glioblastoma from GEO datasets (GSE146463). Quantitative real-time PCR was used to further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Recent reports indicate that circRNA can act as miRNA sponge and interacting with proteins to affect gene expression level to influence transcription and translation [ 37 39 ]. After further analyzing circRNA on breast cancer sample, we found that circ_0047604 expression level is lower in tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports indicate that circRNA can act as miRNA sponge and interacting with proteins to affect gene expression level to influence transcription and translation [ 37 39 ]. After further analyzing circRNA on breast cancer sample, we found that circ_0047604 expression level is lower in tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Different experiments in brain tumors have confirmed tumor suppressor role of miR-324. For instance, SERPINE2 has been found to induce proliferation of glioblastoma cells and inhibit their apoptosis via influencing activity of miR-324-5p/BCL2 axis ( Li et al, 2021 ). Moreover, the oncogenic lncRNA NEAT1 promotes progression of glioma through sponging miR-324-5p and inducing expression of KCTD20 ( Zhang et al, 2021 ).…”
Section: Role Of Mir-324 In Cancersmentioning
confidence: 99%
“…Found that circ-FOXO3 can bind both miR-138-5p and miR-432-5p to regulate NFAT5 expression and thus promote cell proliferation ( Zhang S. et al, 2019 ). Li et al, Found that the circ-SERPINE2-miR-361-3p/miR-324-5p/BCL2 signaling pathway plays an important role in the tumor growth process of GBM ( Li D. et al, 2021 ). Besides, hsa_circ_0008344 ( Zhou et al, 2018 ), hsa_circ_0029426 ( Zhang G. et al, 2019 ), hsa_circ_0067934 ( Xin et al, 2019 ), circ-SKA3 ( Zhou M. et al, 2021 ), circ-PARP4 ( Zhou J. et al, 2021 ), circ-FLN1 ( Sun et al, 2021 ) and circ-NF1( Liu L. et al, 2021 ) were also shown to significantly promote the proliferative capacity and tumor growth of GBM cells, but the specific molecular mechanisms remain to be further explored.…”
Section: Biological Function and Molecular Mechanism Of Circular Rnas In Glioblastomamentioning
confidence: 99%
“…To further analyze the prognostic value of circRNAs in GBM, we evaluated the association of circRNAs expression levels with the overall survival (OS) rate of GBM patients. Twelve upregulated circRNAs were reported to predict poorer OS in GBM patients ( Zhang G. et al, 2019 ; Qian et al, 2019 ; Xin et al, 2019 ; Zhu et al, 2020 ; Chen B. et al, 2021 ; Li D. et al, 2021 ; Liu L. et al, 2021 ; Wang Q. et al, 2021 ; Wu X. et al, 2021 ; Zhou M. et al, 2021 ; Sun et al, 2021 ), and three downregulated circRNAs predicted poorer OS in GBM patients ( Zhang X. et al, 2019 ; Lv et al, 2020 ; Wang T. et al, 2021 ). It was shown that lower expression of has_circ_0067934 was associated with longer disease-free survival (DFS) ( Xin et al, 2019 ).…”
Section: Biological Function and Molecular Mechanism Of Circular Rnas In Glioblastomamentioning
confidence: 99%